Psychological effects on self-medication during the pandemic COVID-19 in WP Labuan: A development of questionnaire and pilot-testing - Michelle L Tan; Shamsur Rahman; Freddie Robinson; Mohd Hijaz Mohd Sani (National Library of Medicine, 2023)
Self-Medication, which is a practice to self-treat using medicine without consulting a medical practitioner or a doctor, is a common practice and the Pandemic Covid-19 may have caused people to resort to self-medication in order to reduce the infectivity of the Covid-19. Objective: To validate and develop an instrument in Bahasa Melayu to assess the psychological distress and self-medication during pandemic Covid-19 in WP Labuan. Methods: A pilot study was conducted among 160 participants in WP Labuan. Reliability testing on internal consistency and content validity was performed on the adapted Covid-19 Peritraumatic Distress Index (CPDI) as well as domain on knowledge, practice and attitude of self-medication. Result: A panel of seven experts evaluated the research instrument for content validity and it was found to have good content item validity. The CPDI domain showed good internal consistency of Cronbach’s Alpha of 0.919. The mean (SD) CPDI score of the respondents in WP Labuan was 32.55 (15.98). 64.2% of the respondents experienced psychological distress. The variable for Area (town/countryside) was found to be statistically significant (p<0.05) to be associated with selfmedication during the pandemic. Conclusion: The instrument established sound reliability and validity and therefore, can be an effective tool for assessing psychological distress and self-medication in the Malaysian population.